Aplikasi Kompos Limbah Bawang Dayak dan FMA untuk Meningkatkan Pertumbuhan dan Hasil Pakcoy di Tanah Gambut: Application of Dayak Onion Waste Compost and AMF to Increase the Growth and Yield of Pakcoy in Peat Soil - Titin Apung Atikah; Rahmawati Budi Mulyani; Juan Fery; Abdul Syahid; Wahyu Widyawati; Yekti Sri Rahayu; Ruben Tingting S (Jurnal Hortikultura Indonesia (JHI), 2024)
This research aims to study the effect of providing Dayak onion harvest waste compost and Arbuscular Mycorrhizal Fungi (AMF) to increase the growth and yield of pak choy in inland peat soil. The method used a Completely Randomized Design (CRD), a 4x4 factorial pattern, and 3 replications. First factor=Dayak onion harvest waste compost (0, 10, 20, 30 ton ha-1). Second factor dose (0, 2, 4, 6 ton ha-1). The interaction treatment of the waste compost at a dose of 20 tons ha-1 and AMF at a dose of 6 tons ha-1 had a significant effect on the growth of the number of leaves at 21 DAS. The waste compost at a dose of 30 tons ha-1 and AMF at a dose of 4 tons ha-1 had a significant effect on plant dry weight. Providing the waste compost at a dose of 30 tons ha-1 had a significant effect over other treatments. At a dose of 20 tons ha-1, it had a significant effect on root length. AMF did not differ significantly in plant height, number of leaves at 14, 21, and 28 DAS, leaf area, plant fresh weight, and plant dry weight. Keywords: Brassica rapa L., compost dosage, harvest waste compost, Completely Randomized Design (CRD), inland peat soil